Case Report: Unusual presentation and atypical course of a case of ureterocolic fistula after anterior resection for sigmoid cancer - Tramontano, Salvatore; Iacone, Biancamaria; Parrella, Valentina; Gargiulo, Antonio; Tedesco, Anna; Bracale, Umberto (Frontiers in Oncology, 2025)
The ureterocolic fistula (UF) can be a rare but serious complication of abdomino-pelvic surgery, gynecological procedures, oncological or inflammatory conditions and, especially in colorectal surgery, it can be due to anastomotic leaks or iatrogenic injuries of the ureter. Treatment is multidisciplinary, often involving endoscopic urological procedures or surgery, when necessary. We present a case of an UF following laparoscopic anterior resection for sigmoid cancer Some peculiar topics, like an early clinical presentation and a rapid resolution with adequate approach, are very interesting and offer good example for suspicion of UF and management. Our patient presented fever and watery diarrhea in 12th POD. CT scan was positive for contrast leakage between the third-low of the left ureter and the rectum. Fistula solved with endoscopic and percutaneous approach, with no need of surgical treatment, thanks to multidisciplinary approach and early treatment.